Solid‐state foaming of isotactic polypropylene and its composites with spherical or fibrous poly(butylenes terephthalate). Issue 15 (19th December 2014) - Luo, Yiwei; Xin, Chunling; Yang, Zhaoping; Yan, Baorui; Li, Zhongpeng; Li, Xiaohu; He, Yadong
ABSTRACT In this article, the foaming behavior of isotactic polypropylene (iPP) and its composites with spherical or fibrous poly(butylenes terephthalate) (PBT) using supercritical CO2 as a blowing agent were investigated. Their foaming performances were also compared in relation to the crystal morphology and rheological behavior of PP. Results demonstrate that crystal structures significantly impacted the cell structures of foams. At relatively low temperature, microcells appeared at the centers of PP spherulites where the melting started. Particularly, bi‐modal cell structure formed in the foamed PP with increasing temperature. However, in the foamed PP composites with spherical or fibrous PBT, this structure almost disappeared due to the smaller PP spherulites. In foaming PP/PBT composites, the heterogeneous nucleation of spherical or fibrous PBT was effective at reducing cell size as well as improving cell density and cell uniformity. The fibrous PBT also acted as scaffolds for preserving cell shapes. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41801.